The Impact of OSCE Implementation on the Stress Level and Performance of Health Science Students - Purnamasari, Elly; Hidayat, Sholeh; Anriani, Nurul (Jurnal Ilmiah Keperawatan Indonesia (JIKI), 2025)
Introduction: Objective Structured Clinical Examination (OSCE) is an evaluation method that is often used in health education to test clinical competence. Aim: This study aims to analyze the impact of the implementation of OSCE on the stress level and academic performance of students of the Faculty of Health Sciences, University of Muhammadiyah Tangerang (Fikes UMT). Methods: This study used a quantitative approach with a cross-sectional design. A total of 150 Fikes UMT students were selected as samples using the purposive sampling technique. Data collection was carried out through academic stress questionnaires and OSCE score results. Data analysis was carried out using paired t-tests and linear regression to determine the relationship between stress and academic performance. Results: There was a significant decrease in student stress levels after the implementation of OSCE (p < 0.001). Before the OSCE, 65% of students experienced high levels of stress, while after the OSCE the number decreased to 40%. In addition, there was a significant negative correlation between stress levels and OSCE values (r = -0.45, p < 0.01), where a decrease in stress levels was associated with improved performance. Conclusion: The implementation of OSCE contributes to lowering students' stress levels and improving their academic performance. Recommendation: Stress management needs to be considered as part of efforts to improve the quality of education in the health sector.